2009
DOI: 10.1161/circulationaha.108.782177
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Pseudoaneurysms of the Thoracic Aorta

Abstract: A 16-year-old girl from an area in Brazil where tuberculosis was endemic was admitted because of recurrent chest pain, progressive dyspnea with exertion, and inability to climb more than 1 flight of stairs. She described fatigue, weight loss, night sweats, and adenopathy of her right axilla and neck during the previous 3 months. On admission she looked distressed, with a heart rate of 76 bpm and blood pressure of 110/55 mm Hg. The ECG demonstrated sinus rhythm with first-degree heart block ( Figure 1).Her admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Various authors have reported atherosclerosis, previous aortic surgery, and mycotic aneurysm as the common aetiology of ABF, 1 , 2 , 6 , 7 while tuberculosis is a rare cause for it. 5 Previous aortic surgery is a common risk factor for pseudoaneurysm formation. It usually occurs at the suture line or at the cannulation site due to iatrogenic defects in the vessel wall and subsequent poor healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors have reported atherosclerosis, previous aortic surgery, and mycotic aneurysm as the common aetiology of ABF, 1 , 2 , 6 , 7 while tuberculosis is a rare cause for it. 5 Previous aortic surgery is a common risk factor for pseudoaneurysm formation. It usually occurs at the suture line or at the cannulation site due to iatrogenic defects in the vessel wall and subsequent poor healing.…”
Section: Discussionmentioning
confidence: 99%
“… 1–4 Tuberculosis related arteritis and pseudoaneurysm is a rare cause of ABF. 5 Massive haemoptysis and exsanguination following its rupture in lung parenchyma can result in acute respiratory distress, hypotension, and death if an emergency intervention is not performed. An endovascular stent-graft repair of the ruptured aorta can be an alternative to conventional surgery, which otherwise carries high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the English literature from 2008 to today revealed 28 more cases (Table 1) [3], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], specifically 18 men and 10 women with a mean age of 44.64 ± 18.16 years (range 16–84). 7 patients had a history of pulmonary tuberculosis and had previously received anti-tuberculosis medication.…”
Section: Discussionmentioning
confidence: 99%